Modeling and experimental validation of 5-level hybrid H-bridge multilevel inverter fed DTC-IM drive - Islam, M.D.; Reza, C.M.F.S.; Mekhilef, Saad (2015)
This paper aims to improve the performance of conventional direct torque control (DTC) drives proposed by Takahashi by extending the idea for 5-level inverter. Hybrid cascaded H-bridge topology is used to achieve inverter voltage vector composed of 5-level of voltage. Although DTC is very popular for its simplicity but it suffers from some disadvantages like- high torque ripple and uncontrollable switching frequency. To compensate these shortcomings conventional DTC strategy is modified for five levels voltage source inverter (VSI). Multilevel hysteresis controller for both flux and torque is used. Optimal voltage vector selection from precise lookup table utilizing 12 sector, 9 torque level and 4 flux level is proposed to improve DTC performance. These voltage references are produced utilizing a hybrid cascaded H-bridge multilevel inverter, where inverter each phase can be realized using multiple dc source. Fuel cells, car batteries or ultra-capacitor are normally the choice of required dc source. Simulation results shows that the DTC drive performance is considerably improved in terms of lower torque and flux ripple and less THD. These have been experimentally evaluated and compared with the basic DTC developed by Takahashi.